Ultra-early neurological deterioration following a brain arteriovenous malformation rupture - Shotar, Eimad; Chiaroni, Pierre-Marie; Haffaf, Idriss; Cortese, Jonathan; Jacquens, Alice; Garzelli, Lorenzo; Allard, Julien; Elhorany, Mahmoud; Amouyal, Caroline; Mathon, Bertrand; Nouet, Aurélien; Premat, Kévin; et al. (Frontiers in Neurology, 2024)
None relative to this study. Pr Frédéric Clarençon reports conflict of interest (unrelated) with Medtronic, Guerbet, Balt Extrusion (payment for readings), Codman Neurovascular (core lab). Dr Nader Sourour is consultant for Medtronic, Balt Extrusion, Microvention (unrelated to the study). Dr Eimad Shotar is principal investigator of a randomized controlled trial related to chronic subdural hematoma embolization financed by a PHRC-IR public grant (unrelated). The other authors report no conflict of interest concerning the materials or methods used in this study or the findings specified in this paper.